Sodium ion battery positive electrode composite material and preparation method thereof

By preparing modified metal oxides and modified conductives, and mixing it with other ingredients, forming a high -performance sodium ion battery orthopedic composite material, solving the problem of irreversible phase change and decline in performance during the cycle. Realize higher electrochemical properties and stability.

CN119340374AInactive Publication Date: 2025-01-21ANHUI NANDU HUATUO NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411713954.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode composite materials have problems such as irreversible phase change, capacity and voltage drop during the cycle, resulting in unsatisfactory electrochemical performance.

Method used

By preparing modified metal oxides and modified conductives, and mixing it with the cross -linked agent, fillers and solvents, forming a high -charging discharge capacity, high circulation, low -power chemical impedance, high magnification performance and high stability Sodium ion battery positive composite material.

Benefits of technology

The charge and discharge capacity, cycle performance and rate performance of the sodium-ion battery cathode composite material are improved, the electrochemical impedance is reduced, and the stability of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340374A_ABST
    Figure CN119340374A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode composite material and a preparation method thereof, belongs to the technical field of positive electrode material processing, and is used for solving the technical problem that the electrochemical performance and the stability of a sodium ion battery positive electrode composite material in the prior art need to be further improved. The preparation method comprises the following steps: preparing a carbonate precursor, further preparing a modified metal salt oxide which has high stability, high conductivity and low electrochemical impedance and is doped with Li < + >, Zn < 2 + >, Mn < 2 + > and Fe < 3 + >, and preparing a modified conductive agent with high charge-discharge capacity, high cycle and high rate performance by doping multi-walled carbon nanotubes with sulfur. The modified metal oxide, the modified conductive agent, the cross-linking agent, the filler and the solvent are uniformly mixed to obtain the sodium ion battery positive electrode composite material with high charge-discharge capacity, high cycle, low electrochemical impedance, high rate capability and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cathode material processing, and in particular to an cathode composite material for a sodium ion battery and a preparation method thereof. Background Art

[0002] Large-scale energy storage is an important support for achieving efficient utilization and promotion of clean energy. However, with the increasing depletion of lithium resources and rising costs, commercial lithium-ion batteries can hardly support the sustainable development of electric vehicles and large-scale energy storage at the same time. Sodium-ion batteries, thanks to the abundant reserves of sodium in nature, low prices and high safety, are expected to become a beneficial supplement to lithium-ion batteries.

[0003] Delmas' first match against N x The electrochemical extraction / insertion reaction of CO2 was reported. x MO2 materials are generally divided into P2 type or O3 type. Studies have shown that in the P2 type structure, sodium ions occupy the prism sites and are transmitted through adjacent prism sites. Therefore, the P2 type has a better transmission rate than the O3 phase, and therefore has better rate performance. Among many layered positive electrode materials, P2-Na 0.67 Ni 0.33 Mn 0.67 O2 has become one of the most promising cathode materials due to its high theoretical capacity, simple synthesis method and environmental friendliness.

[0004] In the prior art, P2-Na 0.67 Ni 0.33 Mn 0.67 The irreversible phase transition, severe capacity and voltage drop of O2 type during the cycle lead to its unsatisfactory electrochemical performance. 0.67 Ni 0.33 Mn 0.67 O2 has a large irreversible capacity loss and low coulombic efficiency. The Mn in the manganese-based positive electrode material in the composite structure 3+ The Jahn-Teller effect caused by this will accelerate the dissolution of active substances, causing the transition metal layer to be distorted and the crystal structure to collapse, thus affecting its electrochemical performance. This is the most common problem in P2-Na 0.67 Ni 0.33 Mn 0.67 The biggest obstacle to the development of O2 positive electrode materials.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a sodium ion battery positive electrode composite material and a preparation method thereof, so as to solve the problem that the electrochemical performance and cycle stability of the sodium ion battery positive electrode composite material in the prior art need to be further improved.

[0007] The purpose of the present invention can be achieved by the following technical scheme: a sodium ion battery positive electrode composite material, comprising the following raw material compositions in parts by weight: 70-80 parts of modified metal oxide, 7-10 parts of modified composite conductive agent, 4-7 parts of cross-linking agent, 1-2 parts of filler and 5-10 parts of solvent.

[0008] Furthermore, the crosslinking agent is one or more of melamine and crosslinked polyaniline; the filler is one or more of single-walled carbon nanotubes, silica, graphite and carbon fiber; and the solvent is N-methylpyrrolidone.

[0009] Furthermore, the preparation method of the modified metal oxide is: after uniformly mixing sodium carbonate, lithium carbonate and a carbonate precursor, heating and calcining are performed to obtain the modified metal oxide.

[0010] Furthermore, the mass ratio of the sodium carbonate, lithium carbonate and carbonate precursor is 0.8:0.05:1.0, and the molecular formula of the carbonate precursor is Mn 0.65 Ni 0.20 Fe 0.15 CO3, the heating and calcining method is: putting a mixture of carbonate precursor, sodium carbonate and lithium carbonate into a tube furnace, raising the temperature of the tube furnace to 900°C, calcining for 12 hours, grinding the calcined product into powder, and passing it through an 800-mesh sieve to obtain a modified metal oxide.

[0011] Furthermore, the preparation method of the carbonate precursor comprises the following steps:

[0012] A1. Mix MnSO4·H2O, NiSO4·6H2O, FeSO4·7H2O and deionized water to obtain a mixed salt solution;

[0013] A2. Add the mixed salt solution into a nitrogen-protected reactor and stir. Raise the temperature of the reactor to 50°C. Add sodium carbonate solution dropwise into the reactor to adjust the pH of the system to 8±0.1. Keep the reaction warm for 5 hours and obtain a carbonate precursor by post-treatment.

[0014] Reaction principle for preparing carbonate precursors: In the reaction system, metal salt solution and sodium carbonate undergo double decomposition reaction, Mn 2+ 、Ni 2+ , Fe 2+ and Na + Exchange with each other and combine to form the difficultly ionized Mn 0.65 Ni 0.20 Fe0.15 CO 3, Make Na in the reaction system + As the concentration decreases, the chemical reaction moves toward Na + The concentration decreases.

[0015] Furthermore, in the step A1, the weight ratio of MnSO4·H2O, NiSO4·6H2O, FeSO4·7H2O and deionized water is 0.65:0.20:0.15:1.00; in the step A2, the sodium carbonate solution is composed of sodium carbonate, ammonium bicarbonate and deionized water in a dosage ratio of 8g:1g:90mL; the dripping rate of the sodium carbonate solution is 20 drops / min, and the post-treatment includes: filtering the reaction solution after precipitation for 24 hours, and drying the washed precipitate at 80°C for 12 hours to obtain a carbonate precursor;

[0016] Furthermore, the preparation method of the modified conductive agent is: placing multi-walled carbon nanotubes in a MgSO4 solution, ultrasonically dispersing at 80°C for 2 hours, and post-treating to obtain sulfur-doped carbon nanotubes.

[0017] Furthermore, the dosage ratio of multi-walled carbon nanotubes and MgSO4 solution is 10g:100mL, and the post-treatment of the sulfur-doped carbon nanotubes includes: placing the ultrasonic solution in a drying oven for 48 hours, placing the mixture of the dried product and MgSO4 solution in a horizontal tube furnace and heating it to 800°C for 60 minutes, and after the reactor cools to room temperature, taking out the reaction product, and obtaining sulfur-doped carbon nanotubes after acid washing and purification.

[0018] The reaction principle of the modified conductive agent is: multi-walled carbon nanotubes are used as raw materials, MgSO4 solution is used as the sulfur source, and sulfur-doped carbon nanotubes are synthesized by high-temperature calcination. MgSO4 reacts with the SP on the multi-walled carbon nanotube material molecules. 2 The orbital hybridization is embedded in the carbon skeleton and connected to the C atoms in a covalent bond manner, forming sulfur doping on the multi-walled carbon nanotubes to prepare sulfur-doped carbon nanotubes.

[0019] The present invention also provides a method for preparing a composite material for a sodium ion battery cathode solution, comprising the following steps:

[0020] S1, mixing and grinding the modified metal oxide, the modified composite conductive agent, the cross-linked polyaniline and the silicon dioxide, and passing through an 800-mesh sieve to obtain a mixture;

[0021] S2. Mix the mixture and N-methylpyrrolidone, and continue stirring for 8 hours to obtain a uniform coating slurry. Evenly coat the coating slurry on aluminum foil, place it in a vacuum drying oven at 80° C. and dry it for 12 hours. Cut it to obtain an electrode sheet.

[0022] The present invention has the following beneficial effects:

[0023] 1. The sodium ion positive electrode composite material prepared by the present invention is a conventional sodium ion battery positive electrode material doped with different proportions of metal cations Li + 、Zn 2+ , Mn 2+ and Fe 3+ The modified material is modified by ultrasonically dispersing multi-walled carbon nanotubes and MgSO4 solution in the prior art, drying and heating to obtain a modified conductive agent, and finally mixing the modified metal oxide, the modified conductive agent, the cross-linking agent, the filler and the solvent to obtain a sodium ion battery positive electrode composite material with high charge and discharge capacity, high cycle, low electrochemical impedance, high rate performance and high stability.

[0024] 2. In the process of preparing a modified metal oxide, the present invention comprises Li + , Mn 2+ 、Ni 2+ and Fe 2+ Reduction of Mn in metal electrode materials by adding carbonate precursors through common precipitation method 3+ content, thereby improving the reversible capacity of the material and making the P2 layered structure more stable. In addition, sodium carbonate solution is used to adjust the pH of the entire system so that the carbonate precursor crystals have high sphericity, good morphology, optimal specific surface area and tap density, thereby improving the safety and structural stability of the material and effectively controlling the battery cost.

[0025] 3. In the process of preparing the modified conductive agent, the present invention combines traditional multi-walled carbon nanotubes with MgSO4 solution, and introduces sulfur into the multi-walled carbon nanotubes by impregnation and calcination method to obtain sulfur-doped carbon nanotubes. The sulfur-doped multi-walled carbon nanotubes have higher specific surface area and conductivity, and reduce the inertness of the surface of the multi-walled carbon nanotubes, so that the capacitance, cycle performance and rate performance of the electrode material are further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 Schematic diagram of transmission electron microscopy of the modified conductive agent of the present invention. DETAILED DESCRIPTION

[0028] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The multi-walled carbon nanotubes used in the present invention refer to the black conductive carbon nanotubes from Shanghai Xiangtian Nanomaterial Co., Ltd., with a specification of 20-30nm / 1kg.

[0030] Example 1

[0031] A method for preparing a sodium ion battery positive electrode composite material in this embodiment comprises the following steps:

[0032] S1. Preparation of modified metal oxides

[0033] Weigh: 8.0 g of sodium carbonate, 1.0 g of sodium bicarbonate and 90 mL of deionized water into a beaker and stir until the system is dissolved to obtain a sodium carbonate solution for later use;

[0034] Weigh: 6.5 g of MnSO4·H2O, 2.0 g of NiSO4·6H2O, 1.5 g of FeSO4·7H2O, and 100 mL of deionized water into a three-necked flask protected by nitrogen, stir until the system is dissolved, raise the temperature of the three-necked flask to 50°C, add sodium carbonate solution dropwise to the three-necked flask at a rate of 20 drops / min, adjust the reaction pH to 8.1, and keep the reaction warm for 5 h. After the reaction is completed, take out the reaction solution, and after 24 h of precipitation, remove the supernatant by suction, wash and dry the precipitate to obtain 12.5 g of carbonate precursor;

[0035] Weigh: 9.6 g of sodium carbonate, 0.6 g of lithium carbonate and 12.0 g of carbonate precursor, mix them evenly and add them into a tubular furnace, heat the tubular furnace to 900° C., calcine for 8 hours, grind the calcined product into powder, and pass it through an 800-mesh sieve to obtain 17.5 g of modified metal oxide.

[0036] S2. Preparation of modified conductive agent

[0037] Weigh: 10.0 g of multi-walled carbon nanotubes were placed in 100 mL of MgSO4 solution at 80°C, ultrasonically dispersed for 2 h, and then dried in an oven for 48 h. The mixture of multi-walled carbon nanotubes and MgSO4 was heated to 800°C in a horizontal tube furnace and maintained for 60 min. After the reactor cooled to room temperature, the reaction product was taken out and purified by acid washing to obtain 13.7 g of modified conductive agent.

[0038] S3. Preparation of positive electrode for sodium ion battery

[0039] Weigh: 17 g of modified transition metal oxide, 1.0 g of cross-linked polyaniline, 1.7 g of modified conductive agent and 0.2 g of silicon dioxide, mix them evenly, and pass through an 800-mesh sieve to obtain a mixture;

[0040] The mixture was mixed with 1.2 mL of N-methylpyrrolidone and stirred for 8 h to obtain a uniform coating slurry. The coating slurry was evenly coated on aluminum foil, dried in a vacuum drying oven at 80° C. for 12 h, and cut to obtain electrode sheets.

[0041] Example 2

[0042] A sodium ion battery positive electrode composite material and a preparation method thereof of this embodiment include the following steps:

[0043] S1. Preparation of modified metal oxides

[0044] Weigh: 8.4 g of sodium carbonate, 1.0 g of sodium bicarbonate and 90 mL of deionized water into a beaker and stir until the system is dissolved to obtain a sodium carbonate solution for later use;

[0045] Weigh: 6.8 g of MnSO4·H2O, 2.1 g of NiSO4·6H2O, 1.6 g of FeSO4·7H2O, and 100 mL of deionized water into a three-necked flask protected by nitrogen, stir until the system is dissolved, raise the temperature of the three-necked flask to 50°C, add sodium carbonate solution dropwise to the three-necked flask at a rate of 20 drops / min, adjust the reaction pH to 8.0, keep the reaction warm for 5 h, take out the reaction solution after the reaction is completed, and after 24 h of precipitation, remove the supernatant by suction, wash and dry the precipitate to obtain 13.8 g of carbonate precursor;

[0046] Weigh: 10.1 g of sodium carbonate, 0.6 g of lithium carbonate and 12.6 g of carbonate precursor, mix them evenly and add them into a tubular furnace, heat the tubular furnace to 900° C., calcine for 8 hours, grind the calcined product into powder, and pass it through an 800-mesh sieve to obtain 21.2 g of modified metal oxide.

[0047] S2. Preparation of modified conductive agent

[0048] Weigh: Place 10.5g of multi-walled carbon nanotubes in 100mL of MgSO4 solution at 80°C, ultrasonically disperse for 2h, and then place in an oven to dry for 48h. Then, heat the mixture of multi-walled carbon nanotubes and MgSO4 to 800°C in a horizontal tube furnace and maintain for 60min. After the reactor cools to room temperature, take out the reaction product, and after acid washing and purification, obtain 14.6g of modified conductive agent.

[0049] S3. Preparation of positive electrode for sodium ion battery

[0050] Weigh: 20 g of modified transition metal oxide, 1.1 g of cross-linked polyaniline, 2.0 g of modified conductive agent and 0.3 g of silicon dioxide, mix them evenly, and pass through an 800-mesh sieve to obtain a mixture;

[0051] The mixture was mixed with 1.4 mL of N-methylpyrrolidone and stirred for 8 h to obtain a uniform coating slurry. The coating slurry was evenly coated on aluminum foil, dried in a vacuum drying oven at 80° C. for 12 h, and cut to obtain electrode sheets.

[0052] Example 3

[0053] A sodium ion battery positive electrode composite material and a preparation method thereof of this embodiment include the following steps:

[0054] S1. Preparation of modified metal oxides

[0055] Weigh: 9.0 g of sodium carbonate, 1.1 g of sodium bicarbonate and 100 mL of deionized water into a beaker and stir until the system is dissolved to obtain a sodium carbonate solution for later use;

[0056] Weigh: MnSO4·H2O 7.3g, NiSO4·6H2O 2.3g, FeSO4·7H2O 1.7g, 100mL deionized water into a nitrogen-protected three-necked flask, stir until the system is dissolved, raise the temperature of the three-necked flask to 50°C, add sodium carbonate solution dropwise to the three-necked flask at a rate of 20 drops / min, adjust the reaction pH to 8.0, keep the reaction warm for 5h, take out the reaction solution after the reaction is completed, after 24h of precipitation, remove the supernatant by suction, wash and dry the precipitate to obtain 11.5g of carbonate precursor;

[0057] Weigh: 10.8 g of sodium carbonate, 0.7 g of lithium carbonate and 13.5 g of carbonate precursor, mix them evenly and add them into a tubular furnace, heat the tubular furnace to 900° C., calcine for 8 hours, grind the calcined product into powder, and pass it through an 800-mesh sieve to obtain 18.3 g of modified metal oxide.

[0058] S2. Preparation of modified conductive agent

[0059] Weigh: 12.0 g of multi-walled carbon nanotubes were placed in 100 mL of MgSO4 solution at 80°C, ultrasonically dispersed for 2 h, and then dried in an oven for 48 h. The mixture of multi-walled carbon nanotubes and MgSO4 was heated to 800°C in a horizontal tube furnace and maintained for 60 min. After the reactor cooled to room temperature, the reaction product was taken out and purified by acid washing to obtain 12.7 g of modified conductive agent.

[0060] S3. Preparation of positive electrode for sodium ion battery

[0061] Weigh: 18.0 g of modified transition metal oxide, 1.0 g of cross-linked polyaniline, 1.8 g of modified conductive agent and 0.3 g of silicon dioxide, mix them evenly, and pass them through an 800-mesh sieve to obtain a mixture;

[0062] The mixture was mixed with 1.3 mL of N-methylpyrrolidone and stirred for 8 h to obtain a uniform coating slurry. The coating slurry was evenly coated on aluminum foil, dried in a vacuum drying oven at 80° C. for 12 h, and cut to obtain electrode sheets.

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 3 is that step S1 is eliminated and Na 0.67 Ni 0.33 Mn 0.67 O2 replaces the modified transition metal oxide in step S3 in an equal amount.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 3 is that step S2 is eliminated and the medium-modified conductive agent in step S3 is replaced by an equal amount of acetylene black.

[0067] Comparative Example 3

[0068] The difference between this comparative example and Example 3 is that no modified conductive agent is added in step S3.

[0069] Performance testing:

[0070] The chemical properties and conductivity of the sodium ion batteries prepared using the sodium ion battery positive electrode composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested, wherein the chemical properties were measured according to the standard SJ / T11793-2022 "Test Method for Electrochemical Properties of Electrode Materials for Ion Batteries", and the conductivity was measured according to the standard SJ / T11792-2022 "Test Method for Conductivity of Electrode Materials for Lithium Ion Batteries". The specific test results are shown in Table 1:

[0071] Table 1 - Test results of samples

[0072]

[0073] Data Analysis:

[0074] Comparative analysis of the data in the above table shows that the rate performance of the sodium ion battery positive electrode composite material prepared by the present invention is improved to 92.3%, the capacity retention rate after 300 cycles is 85.6%, the specific capacity is increased to 155.9 mAh / g, the air stability is 154.6 mAh / g, the conductivity is increased to 0.013 S / cm, and the electrochemical impedance is reduced to 28 mΩ, and all performance parameters are better than those of the comparative example;

[0075] Data description:

[0076] The present invention uses a common precipitation method and a high-temperature calcination method to prepare a carbonate precursor with an excellent crystal structure, thereby improving the stability, conductivity and electrochemical impedance of the modified metal salt oxide, and further improving the charge and discharge capacity, cycle performance and rate performance of the sodium ion battery positive electrode composite material.

[0077] In summary, the present invention is to prepare a modified metal oxide and a modified conductive agent, and evenly mix the two modified raw materials with cross-linked polyaniline, silica and N-methylpyrrolidone to obtain a sodium ion battery positive electrode composite material with high charge and discharge capacity, high cycle, low electrochemical impedance, high rate performance and high stability.

[0078] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A sodium ion battery positive electrode composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 70-80 parts of modified metal oxide, 7-10 parts of modified composite conductive agent, 4-7 parts of cross-linking agent, 1-2 parts of filler and 5-10 parts of solvent.

2. A sodium ion battery positive electrode composite material according to claim 1, characterized in that: The cross-linking agent is one or more of melamine and cross-linked polyaniline; the filler is one or more of single-walled carbon nanotubes, silicon dioxide, graphite and carbon fiber; and the solvent is N-methylpyrrolidone.

3. The sodium ion battery positive electrode composite material according to claim 1, characterized in that: The preparation method of the modified metal oxide is: sodium carbonate, lithium carbonate and a carbonate precursor are mixed evenly, and then heated and calcined to obtain the modified metal oxide.

4. A sodium ion battery positive electrode composite material according to claim 3, characterized in that: The weight ratio of the sodium carbonate, lithium carbonate and carbonate precursor is 0.8:0.05:1.0, and the molecular formula of the carbonate precursor is Mn 0.65 Ni 0.20 Fe 0.15 CO3, the heating and calcining method is: putting a mixture of carbonate precursor, sodium carbonate and lithium carbonate into a tube furnace, raising the temperature of the tube furnace to 900°C, calcining for 12 hours, grinding the calcined product into powder, and passing it through an 800-mesh sieve to obtain a modified metal oxide.

5. The sodium ion battery positive electrode composite material according to claim 3, characterized in that: The method for preparing a carbonate precursor comprises the following steps: A1. Mix MnSO4·H2O, NiSO4·6H2O, FeSO4·7H2O and deionized water to obtain a mixed salt solution; A2. Add the mixed salt solution into a nitrogen-protected reactor and stir. Raise the temperature of the reactor to 50°C. Add sodium carbonate solution dropwise into the reactor to adjust the pH of the system to 8±0.

1. Keep the reaction warm for 5 hours and obtain a carbonate precursor by post-treatment.

6. A sodium ion battery positive electrode composite material according to claim 5, characterized in that: In step A1, the dosage ratio of MnSO4·H2O, NiSO4·6H2O, FeSO4·7H2O and deionized water is 6.5g:2.0g:1.5g:100.0mL; in step A2, the sodium carbonate solution is composed of sodium carbonate, ammonium bicarbonate and deionized water in a dosage ratio of 8g:1g:90mL; the dropping rate of the sodium carbonate solution is 20 drops / min, and the post-treatment includes: filtering the reaction solution after precipitation for 24 hours, and drying the washed precipitate at 80°C for 12 hours to obtain a carbonate precursor.

7. The sodium ion battery positive electrode composite material according to claim 1, characterized in that: The preparation method of the modified composite conductive agent is as follows: placing multi-walled carbon nanotubes in a MgSO4 solution, ultrasonically dispersing the solution at 80°C for 2 hours, and post-treating the solution to obtain sulfur-doped carbon nanotubes.

8. A sodium ion battery positive electrode composite material according to claim 7, characterized in that: The dosage ratio of the multi-walled carbon nanotubes and the MgSO4 solution is 10g:100mL; the post-treatment of the sulfur-doped carbon nanotubes includes: placing the ultrasonicated solution in a drying oven for 48 hours, placing the dried mixture in a horizontal tube furnace and heating it to 800°C for 60 minutes, and after the reactor cools to room temperature, taking out the reaction product, and obtaining sulfur-doped carbon nanotubes after acid washing and purification.

9. The method for preparing a sodium ion battery positive electrode composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing and grinding the modified metal oxide, the modified conductive agent, the cross-linked polyaniline and the silicon dioxide, and passing through an 800-mesh sieve to obtain a mixture; S2. Mix the mixture and N-methylpyrrolidone, and continue stirring for 8 hours to obtain a uniform coating slurry. Evenly coat the coating slurry on aluminum foil, place it in a vacuum drying oven at 80° C. and dry it for 12 hours. Cut it to obtain an electrode sheet.

Citation Information

Cited By

  • Positive electrode composite material of solid-state battery as well as preparation method and application of positive electrode composite material

    CN120657080A